An approach to DEM simulation of hollow torsional shear tests for achieving general loading paths - Ma, Qiang; He, Xiang; Zhou, Yan-Guo; Chen, Yun-Min; Han, Yu-Song (Computers and geotechnics, 2024)
The hollow cylinder apparatus (HCA) is capable of achieving non-proportional stress paths and has been extensively employed to replicate stress paths with rotating principal stress in laboratory element tests. However, only macro-mechanical parameters could be observed in laboratory HCA tests and there is lack of information to understand the evolution of microscale parameters during the loading process. As a promising numerical technique, the discrete element method (DEM) allows investigation of the responses of virtual granular samples under general loading conditions and provides ideal numerical results to overcome the aforementioned limitations. In this study, a novel approach to DEM simulation of the hollow torsional shear apparatus for achieving the general loading paths was introduced. Two algorithms including the stress-controlled and the mixed-controlled loading were developed. Application cases indicated that both undrained monotonic and cyclic loading paths were successfully reproduced by using the proposed algorithms. Compared with results from the literature, DEM results demonstrated that this approach could reasonably reproduce the behaviour of granular material under general loading conditions, including aspects such as dilatancy and pore water pressure generation.